Assisted or Protected Mealtimes? Exploring the impact of hospital mealtime practices on meal intake. (21st March 2016) - Young, Adrienne; Allia, Amy; Jolliffe, Lisa; de Jersey, Susie; Mudge, Alison; McRae, Prue; Banks, Merrilyn
Abstract: Aims: To evaluate the impact of mealtime practices (meal time preparation, assistance and interruptions) on meal intake of inpatients in acute hospital wards. Background: It is common for patients to eat poorly while in hospital, related to patient and illness factors and possibly mealtime practices. Few studies have quantified the impact of mealtime practices on the meal intake of hospital patients. Design: Cross‐sectional study. Methods: Structured observations were conducted at 601 meals across four wards (oncology, medical and orthopaedic and vascular surgical) during 2013. Each ward was observed by two dietitians and/or nurses for two breakfasts, lunches and dinners over 2 weeks. Data were collected on patient positioning, mealtime assistance, interruptions and meal intake (visual estimate of plate waste). Associations between mealtime practices and 'good' intake (prospectively defined as ≥75% of meal) were identified using chi‐squared tests. Results: Sitting up for the meal was associated with good intake, compared with lying in bed. Timely mealtime assistance (within 10 minutes) was associated with good intake, compared with delayed or no assistance. Mealtime interruptions had no impact on intake. Forty percent of patients ( n = 241) ate half or less of their meal, with 10% ( n = 61) eating none of the meal provided. Conclusion: Timely mealtime assistance and positioning for the meal may be important factors that facilitate intake among hospital patients, while mealtime interruptions appeared to have no impact on intake. To improve intake of older inpatients, mealtime programmes should focus on 'assisted mealtimes' rather than only Protected Mealtimes.